PERILAKU INOVATIF GURU DI ERA DIGITAL: PERAN IDENTITAS DIGITAL PROFESIONAL DAN SIKAP PENGGUNAAN TEKNOLOGI - Ragil Prastian; Robin Pratama; Hansein Arif Wijaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of Digital Professional Identity and attitudes toward technology use on innovative behavior among teachers at SMK Negeri 1 Kota Jambi. This study employs a quantitative approach using a survey method administered to 111 teachers via total sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and analyzed using SEM-PLS via SmartPLS 3.0. The results of the study indicate that: (1) Digital competence has a positive and significant effect on attitudes toward technology use (P-values 0.000 < 0.05; T-statistic 6.483 > 1.96). (2) Digital reputation has a positive and significant effect on attitudes toward technology use (P-values 0.027 < 0.05; T-statistic 2.219 > 1.96). (3) Digital ethics and professional responsibility have a positive and significant effect on attitudes toward technology use (P-values 0.000 < 0.05; t-statistic 5.624 > 1.96). (4) Digital ethics and professional responsibility have a positive and significant effect on teachers’ innovative behavior (P-values 0.000 < 0.05; T-statistic 6.112 > 1.96). (5) Attitudes toward technology use have a positive and significant effect on teachers’ innovative behavior (P Values 0.000 < 0.05; T-statistic 4.066 > 1.96).